List of Spanish seamen in ports in the United Kingdom, with particulars of age and qualifications, including other than marine qualifications
C01-0037-001 25 June, 1940. (After Grimsby Transfer). LIST OF SPANISH SEAMEN IN PORTS IN THE UNITED KINGDOM,WITH PARTICULARS OF AGE AND QUALIFICATION, INCLUDING OTHER THAN MARINE QUALIFICATIONS. B = Basque G = Galician S = Spanish. BARRY ......1 B Feliciano BIDEA 26 Engineer BELFAST 16 B Miguel ANDUIZA Suso 26 Officer B Bonifacio ARANGUENA Acha 31 Officer B Bonifacio AZCUNE Mendive 25 Cook, farmer B Ramon de la CRUZ Argote 1st Engineer B Luis DIAZ de Lasaga 54 Captain, clerk B Justo ECHABURU Icaran 1st Engineer B Bonifacio ESTEBAN Garcia Seamen, Carpenter, G Manuel FERNANDEZ Fernandez 40 Sailor, Bricklayer, farmer, B Juan Jose GOMEZ Apraiz Captain fisherman B Jose Maria GONDRA y Ozamiz 28 Officer B Andres GUENECHEA Uranga 44 Cook, chauffeur, fireman B Julian de IRIBAR e Ydoyaga Captain B Perfecto LARRAURI 21 Cook, farmer G Benigno ONTEIRAL Rodriguez 39 Fireman, farmer, fisherman G Jose RAMA Riomayor 42 Boatswain, farmer, fisherman G Jose VIDAL Marins 40 Boatswain, farmer, fisherman BIRKENHEAD 9 B Leon ARRAIBI Estancona 36 Donkeyman B Deogracias BURCANA Guezuriga 20 Cook ? Jose FERNANDEZ Murias 1st Engineer B Jesus LAGAREJOS Larrabide 32 Mechanic B Jose B. MARCAIDA Captain B Pablo YGARTU Sustacha Steward, stock farm worker (BIRKENHEAD TRANSFERRED FROM GRIMSBY). B Lamberto BASARRATE 35 Captain G Manuel FREIRE 30 Chief Engineer B Ignacio IBARZABAL 35 Captain BRISTOL ......2 B Miguel Moral Aguirre Captain Felix R. Pacheco Captain CARDIFF 7 B Alberto AGUIRRE 51 Cook B Santos BASAURI Equsquiaguirre 51 Captain [S] Jose GAVILA y Baya 35 First Mate B Juan LARRASQUITU Torre 53 Captain B Antonio LARRASQUITU Mugica 22 Deck Officer S Jose ORPI Palan 57 Captain S Eduardo del PRADO Rojas 48 First Mate. 292C/946/1/37